Do durum wheat producers benefit of vertical coordination? - Felicetta Carillo (Agricultural and Food Economics, 2017)
Abstract This study aims at assessing if benefits, based on the economic performance of farms operating in an agro-food supply chain, are generated by a vertical coordination. A panel data (2008–2011) of durum wheat producers was used, namely the Italian Farm Accountancy Data Network (FADN). Outcomes of coordinated and non-coordinated farms with equal farm and farmer characteristics were calculated through different economic performance measures. A propensity score-matching model was implemented to take account of the selection bias due to observed individual heterogeneity. The comparisons of average differences in farm economic performance indexes, including costs and profitability, show a coordination premium in competitiveness and profitability of Italian durum wheat farms.